Genome-Wide Association Study for High Milk Yield in Saudi Arabian Dromedary using Whole Genome Sequencing - Faisal M. Alsubaie; Mohanad A. Ibrahim; Suheel Yousuf Wani; Ashraf Awad; Abdulwahed Fahad Alrefaei; Mikhlid H. Almutairi (Advances in Agriculture)
The camels have attracted scientific attention due to their unique agricultural characteristics and are used for a variety of purposes, including milk and meat production. To exploit their full potential, it is essential to improve our understanding of the genetic makeup of these animals. Advances in molecular breeding have expanded our knowledge of the genetic architecture of complex traits through genome-wide association studies (GWAS). This study aimed to identify genome-wide variants, annotate their functions, and examine the genetic variants linked to milk production in camels. We used whole-genome sequencing data of 61 dromedary camels to perform a genome-wide association study for investigated milk traits using a logistic regression model. After variant calling in all 61 genome samples and subsequent rigorous filtering processes, we identified 306,310 single nucleotide polymorphisms (SNPs) across all genomes. Among the 306,310 identified SNPs, a subset of 28 SNPs demonstrated statistical significance (p<5×10−4) in association with milk traits in dromedaries. These significant SNPs were found within 13 locations of candidate genes, namely TYRP1, DLC1, GPC5, SLC24A4, NEMP2, and SLC14A1, suggesting their potential relevance to milk production characteristics in this species. The results of our GWAS unravel the complex genetic landscape of milk production in dromedary camels and provide a list of significant SNPs and candidate genes, providing valuable information for further investigations to understand the molecular mechanisms behind this important economic trait.